THE STRUCTURE OF SUBTIDAL MACROALGAL ASSEMBLAGES AT THE TAMOIOS ECOLOGICAL STATION, A THREATENED CONSERVATION UNIT IN RIO DE JANEIRO, BRAZIL (Brazilian Journal of Oceanography, 2015)
The structure of subtidal rocky bottom communities at Tamoios Ecological Station (TES), situated in Ilha Grande Bay, Rio de Janeiro State, as well as in other Brazilian marine protected areas, is insufficiently characterized. The present study describes the macroalgal assemblages of shallow subtidal rocky bottoms on two islands of the TES-Imboassica (IM) and Búzios Pequena (BP)adopting species and genera as observational units. Two sites were surveyed on each island in summer 2011. Random 30x30 cm quadrats (n=3) were scraped to collect all macroalgae except crustose species. The subtidal assemblages, in which 58 macroalgal species occurred, were characterized by the high frequency and percent cover of Sargassum vulgare C. Agardh (56.8±8.4%). The sites differed significantly in total number of species and Shannon-Weiner diversity index (PERMANOVA, p;5%) were Sargassum, Laurencia, Wrangelia, Canistrocarpus, Asparagopsis, Hypnea, Ceratodictyon, Gayliella, Spyridia and Chondria. Dissimilarities within and between the islands, as shown by nMDS of the cover data, suggest that different spatial scales should be considered in monitoring the rocky bottom communities of Ilha Grande Bay.